Dork Diaries (TV Star) - "Russell,Rachel Renee" (Simon and Schuster,Simon & Schuster: London, 2015)
Nikki Maxwell, Queen of the Dorks, is back in the seventh book of the blockbuster Dork Diaries series - now with over 13 million copies in print! Nikki and her friends are about to have their five minutes of fame! A reality TV crew is going to follow them for the whole month as they record their hit song together. But will the excitement also cause unexpected problems, now that cameras are everywhere Nikki and her friends go? Is life in the spotlight really going to be all they think it is or will it be a Dork Disaster? Full of Nikki's doodles, diary entries and dorkish disasters, get ready to embrace your inner dork with his brand new novel frm the hit series! Perfect for fans of Diary of a Wimpy Kid, Tom Gates and Jacqueline Wilson
Keywords: English, Fiction